Spatial pattern of herbaceous seed dispersal by ungulates in grasslands of Doñana, SW Spain - María José Leiva; Jose María Fedriani (PLoS ONE, 2026)
Most research on endozoochorous seed dispersal by ungulates emphasizes long-distance dispersal and its dependence on ungulate species and habitat heterogeneity. In contrast, the role of ungulate community composition in shaping local (around one hundred hectares or less) spatial patterns in the distribution of plant seeds remains largely unexplored. To address such key question, we quantified ungulate seed dispersal at two grasslands in the Doñana National Park (southwestern Spain). One grassland (Martinazo) was used by a mixed community of four ungulate species (deer, wild boar, cattle, and horses), while the other one (Matasgordas) was used almost exclusively by deer. At each site, a plot was established, and ungulate fecal samples were systematically collected and georeferenced from early spring to mid-summer. The seeds contained in the samples were extracted and identified in the laboratory. Our results revealed clear differences between sites in the total number of dispersed herbaceous seeds (1,302 and 606 seeds in Martinazo and Matasgordas respectively) and the most frequently dispersed plant families. Within the four-species community, cattle and deer differed most in the taxonomic composition of the seeds they dispersed, suggesting that herbivore-specific seed selection and dispersal act as key drivers of grassland structure at fine spatial scales, mirroring dynamics typically observed at broader scales. Moreover, only in the four-ungulate community did we detect significant spatial patterns in seed dispersal. These included positive effects of short-distance feces aggregation, spatial covariance in seed content among nearby feces, and a strong correlation between seed content and local feces density. Seed families predominantly dispersed by cattle also exhibited significant spatial structuring. These findings have important implications for biodiversity management in semi-natural and protected ecosystems, as they demonstrate that the management of ungulate species (both wild and domestic) also influences plant communities. This highlights the need to consider the functional differences among herbivores in ecosystem conservation and restoration strategies.